The feasibility of allergen-specific immunotherapy for bronchial asthma in children with polysensitization - O. V. Trusova; A. V. Kamaev; D. S. Korostovtsev (Аллергология и Иммунология в Педиатрии)
Relevance. There is a shortage of studies that would evaluate the effectiveness of allergen immunotherapy (AIT) in children with bronchial asthma (BA) and polysensitization.The aim of the study: to evaluate AIT effectiveness with house dust mite (HDM) allergens in the treatment of BA in children polysensitized to perennial allergens, based on the dynamics of the symptoms and medications score.Materials and methods. The open prospective controlled study included 36 children aged 9,6 [6,9; 12,3] years (from 6 years 1 months to 14 years 3 months) with moderate atopic asthma (21 children (58%) and mild asthma (15 children (42%) and polysensitization to household allergens. Each patient was observed in the study for 4 years: 1 year of preliminary observation and 3 years of sublingual AIT with D. pteronyssinus and D. farinae (Staloral, Stallergenes Greer, France). For each year of observation, asthma symptoms and medications used were assessed, and the combined Score was calculated. To confirm sensitization, a prick test was performed using a standard method with allergens: house dust, D. pteronyssinus, D. farinae, cat, dog, horse, pillow feather (Biomed, Russia).Results. Over 2 years of AIT, the decrease in the symptom and medication Score was 46,9%, and at the end of 3rd year of therapy, 59,8% (р = 0,0001 from baseline). A decrease in the combined Score exceeding 34.9% compared to baseline was noted in all patients in the study.Conclusion. Sublingual AIT with HDM allergens is highly effective in the treatment of asthma in children with domestic polysensitization, in terms of reducing symptoms of the disease, the need for pharmacotherapy and the combined Score of symptoms and medications. A significant positive effect was registered already from the first year of AIT and continues to increase over subsequent years of therapy.